Does energy consumption reinforce environmental pollution? Evidence from emerging Asian economies - Sharma, Rajesh; Shahbaz, Muhammad; Kautish, Pradeep; Vo, Xuan Vinh (Journal of environmental management, 2021)
Steadily improving per capita income level, energy consumption, and delivery of financial services in South and Southeast Asian countries has remained a subject of discussion among policymakers. Because these endeavors have not only elevated their growth trajectory but also widened the scope for carbon emissions, especially in the preceding two decades. In order to confirm this argument, therefore, in the present study, we intended to examine their dynamic impacts on carbon emissions. In this pursuit, by using the second-generation unit-root test, cointegration test, and panel regression procedures, we investigated the moderating impact of energy solutions on the association between per capita income and CO2 emissions and financial development and CO2 emissions from 1976 to 2015. The computed results revealed that the energy's interaction with the linear per capita income significantly escalated carbon emissions in the long run. However, the impact of energy's interaction with the squared per capita income on carbon emissions is found insignificant but positive in the long run. On the other hand, the interaction of energy with financial development provided a negative but insignificant coefficient. Based on the outcomes, we can ascertain that, at the lower level of income, energy consumption leads to environmental pollution, whereas at the higher level of income, its harmful effect on carbon emissions becomes weak in the given regions. By taking a cue from the computed results, we proposed a policy framework that might help these regions to navigate the energy-led environmental challenges in the coming years. Examining the direct and moderating role of energy solutions on the carbon emissions in the eleven developing countries of Asia. Notes: Regular lines are used to represent the direct effects, whereas, the dotted lines represent the interaction effect. Here (+) = positive impact, (−) = negative impact, sig. = significant influence, and insig. = insignificant influence. [Display omitted] •The direct and moderating impacts of energy consumption on CO2 emissions are investigated.•The interaction between energy solutions and per capita income raised CO2 emissions.•The interaction between financial development and energy solutions had a negative and insignificant impact on CO2 emissions.•Per capita income, energy solutions, and financial development intensified carbon emissions.